Rapid preparation of high-performance S0.4Co4Sb11.2Te0.8 skutterudites with a highly porous structure. Issue 8 (July 2021) - Jin, Di; Ruan, Zheng; Duan, Bo; Li, Jialiang; Zhai, Pengcheng; Yang, Houjiang; Wang, Hongtao; Li, Guodong; Zhou, Ling
Highlights: Porous S0.4 Co4 Sb11.2 Te0.8 skutterudite is prepared by OS-HP with sectional pressure. A highly porous structure considerably reduces the lattice thermal conductivity. Pressure relief treatment promotes the formation of intracrystalline pores. Abstract: In this study, S0.4 Co4 Sb11.2 Te0.8 skutterudites with a highly porous structure inside grains are prepared by a one-step hot-pressing (OS-HP) method. The effect of the pressure relief treatment at the heating stage on the micro-morphology and thermoelectric properties of materials is investigated. When the temperature corresponding to the pressure relief treatment is less than 723 K, the grain size dramatically increases from ∼1 to ∼50 μm, and a large number of pores are distributed inside these large grains. Compared with those samples prepared by the conventional method, the thermal conductivity of samples prepared by the pressure relief treatment is significantly reduced due to the high porosity. The ZT values of samples prepared by the pressure relief treatment are greater than 1.6 at 825 K. This newly developed OS-HP method can be employed for the rapid fabrication of highly porous structured skutterudites with low-melting-point compositions as well as of other material systems.